Medium- and long-term prognostic validity of competing classification proposals for the former somatoform disorders - Schumacher, S.; Rief, W.; Klaus, K.; Brähler, E.; Mewes, R. (Psychological medicine, 2017)
DSM-5 introduced a fundamental revision of the category of somatoform disorders, which resulted in the new somatic symptom disorder (SSD) and related disorders. However, prognostic validity of SSD remains unclear, while other classification proposals, such as bodily distress disorder (BDD) or polysymptomatic distress disorder (PSDD), might be promising alternatives for the new ICD-11. Therefore, the comparison of the different approaches concerning long-term prognosis of disorder-relevant factors is of special interest. In a longitudinal design (baseline, 1-year, and 4-year follow-up), the three proposals (SSD, BDD, PSDD) were compared in an age-representative sample of the German general population (N = 321). To this end, the baseline sample was divided into three independent pairs of groups (with/without SSD, with/without BDD, with/without PSDD). It was tested how well each approach differentiated with regard to medium- and long-term healthcare utilization, number of symptoms, and impairment. Criteria for BDD distinguished best with regard to future healthcare utilization resulting in a large-sized effect (f = 0.44) for the difference between persons with and without BDD, while SSD and PSDD revealed only medium-sized effects (f = 0.28 and f = 0.32) between subjects with and without diagnosis. The three proposals distinguished equally well with regard to future subjective impairment (between f = 0.39 and f = 0.41) and the number of reported symptoms (between f = 0.77 and f = 0.83). In accordance with our data regarding prognostic validity, the current draft of the WHO group is based on the BDD proposal. However, existing limitations and weaknesses of the present proposal for the ICD-11 are further discussed.